(untitled) (Research, Society and Development, 2025)
Facial harmonization involves various procedures used as an adjunct to treatments that promote aesthetic improvement of the face and help with rejuvenation. These procedures range from the application of substances such as botulinum toxin, hyaluronic acid and collagen, to the dermal application of threads, such as lifting, intending to reduce wrinkles and expression lines. For health professionals to be qualified in these types of procedures and be successful in their treatments they must know the anatomy, position location of the facial muscles as well as their topographical relationships with other structures such as arteries, veins and nerves. The aim of this study is to present a bibliographic survey of articles that demonstrate the importance of facial anatomical knowledge when performing aesthetic procedures. A systematic review was carried out on the PubMed and MedLine databases. Using descriptors such as: “facial muscles”, “aesthetics”, “hyaluronic acid”, “botulinum toxin”, “collagen” and “harmonization”, combined with each other with “AND” and “OR” connectors, in the English and Portuguese languages, from Brazil, a total of 32 final articles were reached; which show how important it is for professionals to have anatomical knowledge of facial muscles and how essential it is for carrying out safe and precise procedures, as the inappropriate application of substances can cause adverse effects, from the mildest to the most severe. The articles consulted all agree on the importance of training the professionals who carry out these procedures.